ISIS DALAM TINJAUAN AQIDAH ISLAMIYAH - Semjan Putra, Ali Musri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2014)
Islam is a peaceful and just religion even to the non-muslims. Therefore, Islam prohibits wrongdoing to anyone, even to animal. Whoever reads the Islamic literatures that were written by the classic scholars will find this matter clearly. Even the word Islam itself means peace or salvation. But, nowadays, the beauty of this Islamic teaching is covered by the dust and fog of thoughts that deviate from the pure Islamic teaching. One of them is ISIS, which recently becomes an issue that stirs people in the world. So, in this call paper that the author proposes, the forms of deviation of ISIS will be discussed from the point of view of Islamic creed based on the valid proofs from the Qur'an and shahih hadits. Keyword: ISIS, Tinjauan, Aqidah Islamiyah.